Sunbed Use among 11- to 17-Year-Olds and Estimated Number of Commercial Sunbeds in England with Implications for a 'Buy-Back' Scheme - Louisa G. Gordon; Rob Hainsworth; Martin Eden; Tracy Epton; Paul Lorigan; Megan Grant; Adéle C. Green; Katherine Payne (MDPI AG, 2021)
Prior to 2011 legislation prohibiting children from using commercial sunbeds, the prevalence of sunbed use in 15- to 17-year-olds in some areas in England was as high as 50%. Despite significant decreases since 2011, children today still practice indoor tanning. We estimated current sunbed use in 11- to 17-year-olds in England, the number of available commercial sunbed units, and the associated cost of a 'buy-back' scheme to remove commercial sunbeds under a potential future policy to ban sunbeds. We undertook a calibration approach based on published prevalence rates in English adults and other sources. Internet searches were undertaken to estimate the number of sunbed providers in Greater Manchester, then we extrapolated this to England. Estimated mean prevalence of sunbed use was 0.6% for 11- to 14-year-olds and 2.5% for 15- to 17-year-olds, equating to 62,130 children using sunbeds in England. A predicted 2958 premises and 17,865 sunbeds exist nationally and a 'buy-back' scheme would cost approximately GBP 21.7 million. Public health concerns remain greatest for 11- to 17-year-olds who are particularly vulnerable to developing skin cancers after high ultraviolet exposure.